Western horses and competition statistics in Hungary with special regard to the Quarter Horse - Meinhardt, Sarolta; Horvainé Szabó, Mária; Tóthné Maros, Katalin (Animal welfare, Ethology and Housing Systems (AWETH), 2025)
In our country, the riding style of Western riding is becoming increasingly popular over the last 10 years. The Hungarian Equestrian Association officially recognized the Western Discipline in 2000 (Pető Zoltán, personal communication). The most popular breed of western riding is the quarter horse (http1). The breed was bred in America in 18-19. century for short races (quarter mile). In my thesis, I analysed the datas from the western national championships of 2013, 2014 and 2015. The most popular competiton style was reining. Quarter horses became more and more popular among the riders. In 2013, 58% of the riders rode quarter horses, in 2014 63%, and in 2015 66% of them chose this breed. Western cutting, reining and cattle penning were accomplished predominantly with quarter horses (90%, 85%, and 63% respectively). According to the datas the quarter horse breed is becoming more and more popular among the Hungarian western riders. In a questionnaire survey, I asked questions about the practice of western horse keeping, feeding, training & competing and also about their „bad” habits (i.e. stereotypies). According to the answers, 2/3 of the horses are kept in box or „running box” and 54% of the horses are pastured during the day (on an average of 8 hours per day). Western riders work 4-5 times a week with their horses and 65% of them take part in competitions. Most of the horses (90%) are reported not having any bad habits.